Analysis of Risk Factors for Otitis Media with Effusion in Children with Adenoid Hypertrophy - Yang A; Jv M; Zhang J; Hu Y; Mi J; Hong H (Dove Medical Press, 2023)
Anni Yang,1,* Menglei Jv,2,* Jun Zhang,1,* Yuqi Hu,1 Jiaoping Mi,1 Haiyu Hong1 1Allergy Center, Department of Otolaryngology Head and Neck Surgery, The Fifth Affiliated Hospital of Sun Yat-sen University, Zhuhai, People's Republic of China; 2Department of Nephrology, The Fifth Affiliated Hospital of Sun Yat-sen University, Zhuhai, People's Republic of China*These authors contributed equally to this workCorrespondence: Haiyu Hong, Allergy Center, Department of Otorhinolaryngology Hospital, The Fifth Affiliated Hospital of Sun Yat-sen University, Zhuhai, People's Republic of China, Email honghy@sysu.edu.cnObjective: This study aimed to explore whether children with AH have a higher obesity prevalence and analyze the risk factors for otitis media with effusion(OME) in AH children.Methods: AH patients aged 3- 12 years old that were hospitalized in our hospital for adenoidectomy from June 2020 to September 2022 were included in this study. Height and weight were measured to calculate the body mass index, weight for height and weight z-score to evaluate the development of AH children. Propensity score matching was applied to minimize patient selection bias and adjust for confounding factors to analyze the risk factors for OME in children with AH.Results: A total of 887 children with AH were enrolled in this study. The prevalence of overweight or obesity was higher in children with AH than the control group. The size of adenoids is significantly different between AH children with and without OME. For children aged over 5, there are significantly higher counts of white blood cells, neutrophils, and monocytes in the AH children with OME than those without OME. More individuals represent to be atopic in children with OME than those without OME.Conclusion: The obstruction of the Eustachian tube is the most important factor of OME in AH children. It seems that there is no apparent correlation between OME and atopic conditions in AH children. In addition to surgical resection of adenoids, active control of infection and inflammation are also important to prevent OME for AH children aged over 5.Keywords: adenoid hypertrophy, otitis media with effusion, risk factors, atopic conditions